KFC Malaysia / Nurul Najwa Ghani … [et al.] - Ghani, Nurul Najwa; Mohd Rosli, Nabilla Affiqqah; Sobri, Siti Rubaani (2020)
Kentucky Fried Chicken (KFC) Malaysia is a major Quick Service Restaurant (QSR) operator in Malaysia and has been established for just over 20 years now. It serves mainly chicken related items, but offers side dishes to its consumers as well. Lately, more and more Malaysians have been opting for a healthier eating diet as a large number of them have become more health conscious. This has opened the door for KFC's main competitors, such as McDonald's, to come out with a new range of healthier products, allowing them to mount a greater challenge on KFC Malaysia's current position as Malaysia's leading fast food operator. As a response to the advancement made by KFC's competitors in providing healthier fast food, KFC are to introduce a new set of healthier products that would be mainly target market health conscious people, living in Malaysia. Its target market would largely be based on segmentation of age, where it would be focused on customers in the age group of between 4 to 40 years old. KFC Malaysia would, nevertheless, have to fight off fierce competition from other fast food operators, such as Kenny Roger's, Burger King, A&W, Radix Chicken and KFC's biggest rival, McDonald's, who are also trying to take hold of the new market of healthier products. The new healthier menu that KFC Malaysia is going to introduce would not only be a new healthier alternative to its existing products, but also an addition to what it already has to offer. The pricing• and promotion strategies would also be looked into as KFC Malaysia prepares to introduce its new healthier menu to the public.